Bats of a feather: Range characteristics and wing morphology predict phylogeographic breaks in volant vertebrates - Sydney K. Decker; Kaiya L. Provost; Bryan C. Carstens (Frontiers of Biogeography)
Intraspecific genetic variation and phylogeographic structure can be influenced by factors such as landscape features, environmental gradients, historical biogeography and organismal traits such as dispersal ability. Since deep genetic structure is often considered a precursor to speciation, identifying the factors that are associated with genetic structure can contribute to a greater understanding about diversification. Here, we use repurposed data to perform a global analysis of volant vertebrates (i.e. bats and birds) to estimate where intraspecific phylogeographic breaks occur and to identify the factors that are important predictors of these breaks. We estimate phylogeographic breaks using Monmonier’s maximum difference barrier algorithm and conduct a random forests analysis using the presence of a phylogeographic break as a response variable. In bats, phylogeographic breaks are concentrated in biodiversity hotspots while breaks estimated in bird species are more widespread across temperate and tropical zones. However, for both clades, geographical features such as maximum latitude, measures of wing morphology and organismal traits associated with feeding ecology were found to be important predictors of phylogeographic breaks. Our analysis identifies geographical areas and suites of organismal traits that could serve as a starting point for more detailed studies of biodiversity processes. Highlights Phylogeographic breaks, particularly in species with high dispersal ability, are of interest to evolutionary biologists as a potential precursor to speciation. Repurposed data can be used to identify large-scale trends in biodiversity. Monmonier’s maximum differences algorithm can be employed to estimate phylogeographic breaks using georeferenced sequence data. For volant vertebrates, phylogeographic breaks are predicted by aspects of geographic range, wing morphology and feeding ecology. In bats, breaks are concentrated in tropical biodiversity hotspots while phylogeographic breaks in birds are more evenly distributed across temperate zones.